Thermoelectric Properties and a Defective Subsystem of Heterophasic Materials on the Basis of a Lead Telluride with Impurity of Antimony - Prokopiv, V.V.; Galushchak, M.O.; Horichok, I.V.; Parashchuk, T.O.; Matkivskiy, O.M.; Bachuk, V.V.; Dzumedzey, R.O. (Physics and Chemistry of Solid State, 2019)
The results of the study of thermoelectric properties and the defective subsystem of lead telluride doped by antimony PbTe:Sb (8%), promising material for the creation of heat energy converters on their basis. The regularities in the behavior of the properties investigated, which are due to the biphasicity of the material and the significant influence of the technological factors of obtaining samples on their defective subsystem, are established. The modeling of the defect subsystem of PbTe:Sb crystals was carried out taking into account thepresence of additional phase inclusions and it was found that dominant point defects are internode atoms of antimony.